Dividend taxes and income shifting - Annette Alstadsæter; Martin Jacob (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
This paper analyzes whether a dividend tax cut for owner-managers of closely held corporations encourages income shifting, income generation, or both. We use rich, micro data from Sweden for the period 2000 - 2011 comprising the entire Swedish population, as well as firmand individual-level data for all owner-managers in closely held corporations, partnerships, and self-employed. We find robust evidence of extensive income shifting across tax bases in response to the 2006 dividend tax cut. Relative to owners of unincorporated businesses, owner-managers of closely held corporations do not increase total income. Instead, they relabel earned income as dividend income. The income shifting effect is stronger for owner-managers with tax incentives and with easier access to income shifting through a high ownership share.
Keywords: H21; H25; H3; 330; income shifting; income generation; dividend taxes; closely held corporations; owner-managers